Moderating role of job control on the response of ambulatory blood pressure to variation in daily work load - Melamed, S.; Kristal-Boneh, E.; Harari, G.; Froom, P.; Ribak, J. (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'This quasi-experimental study tested the ambulatory blood pressure responsivity to daily variation in the work load of the same workers and examined whether this responsivity is moderated by perceived job control.' ' METHODS ': 'The subjects were 79 nonshift, normotensive men who reported nearly almost equal occurrences of low and high work load in a typical workday. Job control was assessed by questionnaire. The workers recorded their situational work load and other parameters at each recording of ambulatory blood pressure.' ' RESULTS ': 'An analysis of covariance showed the main effects of both situational work load and job control on systolic ambulatory blood pressure, as well as a significant work load by job control interaction, even after control for clinic blood pressure, age, and body mass index. A blood pressure response to increased work load was observed only for workers with low job control. These workers also had a higher average systolic ambulatory blood pressure than workers reporting high control. The difference was 6.2 mm Hg (0.82 kPa) during the low workload periods and 10.2 mm Hg (1.36 kPa) during the high workload periods. A further multiple regression analysis confirmed the interaction and the main effect of job control but not that of work load, after control for work-related activities, body position, and hour of examination.' ' CONCLUSION ': 'This study showed that ambulatory blood pressure at work can fluctuate with variations in work load but only for workers with low job control. Low job control is independently associated with higher systolic ambulatory blood pressure.
Keywords: job strain; responsivity